Colonoscopy quality measures: experience from the NHS Bowel Cancer Screening Programme. Issue 7 (22nd September 2011) - Lee, Thomas J W; Rutter, Matthew D; Blanks, Roger G; Moss, Sue M; Goddard, Andrew F; Chilton, Andrew; Nickerson, Claire; McNally, Richard J Q; Patnick, Julietta; Rees, Colin J
Abstract : Objectives: Colonoscopy is central to colorectal cancer (CRC) screening. Success of CRC screening is dependent on colonoscopy quality. The NHS Bowel Cancer Screening Programme (BCSP) offers biennial faecal occult blood (FOB) testing to 60–74 year olds and colonoscopy to those with positive FOB tests. All colonoscopists in the screening programme are required to meet predetermined standards before starting screening and are subject to ongoing quality assurance. In this study, the authors examine the quality of colonoscopy in the NHS BCSP and describe new and established measures to assess and maintain quality. Design: The NHS BCSP database collects detailed data on all screening colonoscopies. Prospectively collected data from the first 3 years of the programme (August 2006 to August 2009) were analysed. Colonoscopy quality indicators (adenoma detection rate (ADR), polyp detection rate, colonoscopy withdrawal time, caecal intubation rate, rectal retroversion rate, polyp retrieval rate, mean sedation doses, patient comfort scores, bowel preparation quality and adverse event incidence) were calculated along with measures of total adenoma detection. Results: 2 269 983 individuals returned FOB tests leading to 36 460 colonoscopies. Mean unadjusted caecal intubation rate was 95.2%, and mean withdrawal time for normal procedures was 9.2 min. The mean ADR per colonoscopist was 46.5%. The mean number of adenomas per procedure (MAP) was 0.91; the mean number of adenomas per positive procedure (MAP+) was 1.94. Perforation occurred after 0.09% of procedures. There were no procedure-related deaths. Conclusions: The NHS BCSP provides high-quality colonoscopy, as demonstrated by high caecal intubation rate, ADR and comfort scores, and low adverse event rates. Quality is achieved by ensuring BCSP colonoscopists meet a high standard before starting screening and through ongoing quality assurance. Measuring total adenoma detection (MAP and MAP+) as adjuncts to ADR may further enhance quality assurance.